Heidelberg integrated samples 2018-2020 and pseudo power plant experiment results [data] - Maier, Fabian; Gerbig, Christoph; Levin, Ingeborg; Super, Ingrid; Marshall, Julia; Hammer, Samuel (Universität, 2021)
These data files show the measurement and model ffCO2 results (surface source influence vs. volume source influence approach) for the two-week inte...
Gesehen am 09.03.2022
Keywords: Forschungsdaten; Datenbank